Evaluating the Implementation of the Passive House Concept for Sustainable Building Construction in Nigeria - Keftin, N. A.; Yerima, A. A. (Theory and Applications of Engineering Research Vol. 6, 2024)
This study seeks to determine whether stakeholders in the building industry in Nigeria have adequate information about Passive House Concept and whether they consider principles of passive design in planning and construction of building projects in addition to challenges affecting implementation of the concept. Major shifts in population from rural to urban environments, in conjunction with climate change, are recognised by international organisations to have intensified pressure on ecosystems. The current state of the ecosystem throughout the world is a result of natural resources being consumed at a rate that is faster than sustainable. The construction industry makes a significant contribution in this area, and it is anticipated that it will adopt efficient and effective modes and standard forms of construction processes, operation, and maintenance activities for sustainability in resource consumption and a balanced ecosystem. Passive House is a building, which is designed and constructed using the Passive House Planning Package (PHPP). It is a building standard that is truly energy efficient, comfortable and ecological at the same time. Professionals and property owners were identified as sources of data information. The Statistical Package for Social Scientist (SPSS) package was used in analyzing the data collected at 5% level of confidence. According to the findings, just 28% and 22%, respectively, of the professionals and owners who replied claimed to be knowledgeable about and aware of PHPP. However, it is positive that fundamental passive concepts for humidity control and cooling are being taken into account during the design and building process. The main contribution of this research to knowledge of sustainability in construction works is the revelation of the lack of information and capacity about passive house construction in Nigeria, hence the proposal of the need for more information about Passive House and its concept to be made available.